Mikrohistoria na obrzeżach metanarracji : list Marii Kuńskiej z Brzeska do Bolesława Bieruta w związku z akcją "Wisła" - Syrnyk, Jarosław (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2020)
The inspiration to write the article has been provided by a source document – a letter from a woman from Besko to Polish president Bolesław Bierut with a request to be exempted from displacement during Operation Vistula, launched in April 1947. An analysis of the document, employing the thick description method, resulted in working conclusions pertaining both the specific event and the context in which it occurred, as well as conclusions concerning potential new research fields.
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne